Whole Cottonseed as an Effective Strategy to Mitigate Enteric Methane Emissions in Cattle Fed Low-Quality Forages - Hernandez, Olegario (2025)
This study evaluated enteric methane (CH₄) emissions, dry matter intake (DMI), and performance in rearing beef heifers fed either a Guinea-grass-only diet (0WCS) or Guinea grass supplemented with whole cottonseed (WCS) at 0.5% of body weight (BW). Twenty-four Braford heifers were randomly allocated into four pens (three animals per pen) per treatment over two experimental periods. Methane emissions were measured using the SF₆ tracer technique. Heifers receiving WCS supplementation produced 29% less CH₄ (120.64 vs. 169.54 g/day for 0.5WCS and 0WCS, respectively; p = 0.02) and showed a 22% reduction in CH₄ yield (7.30% vs. 9.41% of gross energy intake; p = 0.02). Methane intensity was 33% lower in supplemented heifers (0.37 vs. 0.55 g CH₄/kg BW; p = 0.01). However, WCS supplementation significantly reduced total DMI and forage DMI (p = 0.01 and p < 0.01, respectively). In terms of performance, heifers in the 0.5WCS group gained 0.28 kg/day, while those in the 0WCS group lost 0.10 kg/day. These results indicate that WCS supplementation mitigates CH₄ emissions while improving weight gain in beef heifers fed low-quality forage diets, making it a promising strategy for enhancing the sustainability of beef cattle production systems.